Relevansi Supremasi Kristus Bagi Pemberitaan Injil di Indonesia: Eksegesis Injil Yohanes 14:6 - Kalis Stevanus (KAMASEAN: Jurnal Teologi Kristen, 2021)
Abstract; The discussion of the preaching of the gospel cannot be separated from the doctrine of the supremacy of Christ as the only way of salvation. In the context of a pluralist Indonesian society, the author tries to give an understanding of the supremacy of Christ and its relevance to the preaching of the Gospel based on John 14:6 so that Christians are not influenced by pluralism. Through the exegetical approach to the text of the Gospel of John 14:6, it is obtained the meaning of the supremacy of Christ which is stated by John that He is the only way of salvation or the true Savior. This is a relevant message to be expressed in the ministry of preaching the gospel. Abstrak; pembahasan mengenai pemberitaan Injil tidak dapat dipisahkan dari doktrin tentang supremasi Kristus sebagai satu-satunya jalan keselamatan. Dalam konteks masyarakat Indonesia yang pluralis, penulis mencoba untuk memberi pemahaman tentang supremasi Kristus dan relevansinya bagi pemberitaan Injil berdasarkan Yohanes 14:6 sehingga umat Kristen tidak terpengaruh pluralisme. Melalui pendekatan eksegetikal pada teks Injil Yohanes 14:6 tersebut diperoleh makna tentang supremasi Kristus yang dinyatakan Yohanes bahwa Dia adalah satu-satunya jalan keselamatan atau Juruselamat sejati. Hal ini menjadi berita yang relevan untuk dinyatakan dalam pelayanan pemberitaan Injil.